2017
DOI: 10.3390/min7090172
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption and Magnesium Carbonate Precipitation in MgCl2–NH3–NH4Cl Solutions: Implications for Carbon Capture and Storage

Abstract: CO 2 absorption and carbonate precipitation are the two core processes controlling the reaction rate and path of CO 2 mineral sequestration. Whereas previous studies have focused on testing reactive crystallization and precipitation kinetics, much less attention has been paid to absorption, the key process determining the removal efficiency of CO 2 . In this study, adopting a novel wetted wall column reactor, we systematically explore the rates and mechanisms of carbon transformation from CO 2 gas to carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…This is particularly important in the context of CCS, where flue gases from power plants are injected into geological formations for long-term storage. 107 Flue gases, which are produced during the combustion of fossil fuels, contain various components like CO 2 , NO X , SO X , and trace gases. When injected into the reservoir during EOR operations, these gases can interact with the minerals present in the formation, leading to dissolution and precipitation reactions.…”
Section: Numerical Simulation Of Geochemical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in the context of CCS, where flue gases from power plants are injected into geological formations for long-term storage. 107 Flue gases, which are produced during the combustion of fossil fuels, contain various components like CO 2 , NO X , SO X , and trace gases. When injected into the reservoir during EOR operations, these gases can interact with the minerals present in the formation, leading to dissolution and precipitation reactions.…”
Section: Numerical Simulation Of Geochemical Reactionsmentioning
confidence: 99%
“…The software also enables the modeling of the effects of other components present in flue gases, such as nitrogen oxides (NO X ) and sulfur oxides (SO X ), on the kinetics of geochemical reactions. This is particularly important in the context of CCS, where flue gases from power plants are injected into geological formations for long-term storage . Flue gases, which are produced during the combustion of fossil fuels, contain various components like CO 2 , NO X , SO X , and trace gases.…”
Section: Numerical Modeling and Simulation Of Flue Gas Injectionmentioning
confidence: 99%
“…This could be explained by the length of alkyl chain and the van der Waals force between the precipitates and the additive and also the polar interaction from the hydrophilic groups which can transform the polymorphs. Zhu et al (2017) studied the MgCl2-NH3-NH4Cl system for CO2 mineralisation with a wetted wall column reactor. It was found that the diffusion of the reactants in the liquid film was the rate-limiting step based on the kinetics study.…”
Section: Product Evaluationmentioning
confidence: 99%
“…On solid interfaces, metal oxide surfaces have been shown to have a high absorption capacity for CO 2 . Magnesium oxide (MgO) and calcium oxide (CaO), present in various water sources, are the preferred materials for CO 2 capture due to the high absorption rates of Mg 2+ and Ca 2+ . Other studies have shown that metal hydroxides (Fe­(OH) 2 , Co­(OH) 2 , and Ni­(OH) 2 ) are efficient adsorbents for capturing CO 2 , producing metal carbonate (MCO 3 ) and H 2 O as products . Correlations have been found between CO 2 uptake and humidity, where water dissociation provides basic OH sites for reaction with the acidic CO 2 . ,, Studies have shown that oxide supports modified with other alkali metals have a high capacity for CO 2 adsorption .…”
Section: Introductionmentioning
confidence: 99%